Psychosocial rehabilitation programmes in mental health: the perceived impact of a psychosocial rehabilitation programme on the recovery of persons with a history of mental illness - Madatt, Musiegh (Department of Social Development, 2022)
This study explored psychosocial rehabilitation programmes in mental health and investigated the perceived impact of participation in a psychosocial rehabilitation (PSR) programme on the recovery of persons with a history of mental illness. The study focused on how their participation in psychosocial rehabilitation programmes impacted the well-being of the mental health users individually and socially as well as their perceptions of the benefits and or disadvantages of participation in the programmes as well as their recommendations for improvements. A qualitative explorative research design was applied. Sixteen participants were selected using purposive sampling and data collected by means of face-to-face semi-structured interviewing. The data obtained was analysed using qualitative methods. Most significantly the findings of this study further supports the value of psychosocial rehabilitation programmes for mental health users. Most notably improved individual personal development and independence. Social wellbeing improvements were found with an emphasis on growth in confidence to approaching further socialisation, improvements in the quality of individual relationships and the expansion of support networks. No significant critique of the programmes was identified and the most significant improvements recommended related to the expanding of interactive activities such as more peer socialisation and recreational activities to further the therapeutic value experienced in them. The most important recommendations from the findings include expanding PSR, incorporating PSR programmes into the public service, encouraging PSR programmes through supportive legislation, integrating families more in PSR programmes, expanding research on the outcomes of PSR within a South African context and exploring research that includes the perspectives of the family members living and caring for individuals with mental illness